The contribution of massive fetomaternal hemorrhage to antepartum stillbirth: a 25‐year cross‐sectional study. (16th September 2015) - O'Leary, Bobby D.; Walsh, Colin A.; Fitzgerald, Joan M.; Downey, Paul; McAuliffe, Fionnuala M.
Abstract: Introduction: Fatal antepartum fetomaternal hemorrhage is a relatively uncommon clinical presentation, though one that appears quickly and without warning. The pathophysiology of this disease is unclear, and the incidence does not appear to be decreasing in line with overall antepartum mortality. This study was undertaken to analyse trends in antepartum fetal death from fetomaternal hemorrhage over a 25‐year period in a single maternity hospital in Dublin, Ireland. Material and methods: A cross‐sectional study of 192 132 nonanomalous infants weighing 500 g or more, delivered in a single tertiary‐referral university institution between 1987 and 2011. Data was compared using Fisher's exact test, univariate analysis, and Cuzick's test for trend. Results: There was no decrease in the rate of fatal fetomaternal hemorrhage over the past 25 years ( p = 0.29), despite a decline in overall antepartum deaths ( p = 0.0049). Fetomaternal hemorrhage accounted for 4.1% (34/828) of antepartum stillbirths. A higher proportion of these stillbirths occurred at term gestations (74%; 25/34) compared with other causes (40%; 321/794; p = 0.0003). Female infants were statistically more likely to be involved than males [odds ratio (OR) 2.33, 95% confidence interval (CI) 1.08–5.47, p = 0.02). Multiple gestations were up to six times as likely to be affected as singleton pregnancies (OR 6.52, 95% CI 1.67–18.50, p = 0.005). Conclusions: Over the past 25 years there has been no reduction in rates of fatal fetomaternal hemorrhage. Female infants and multiple gestations remain at higher risk of antepartum death from fatal fetomaternal hemorrhage.